Nano-Zinc Oxide Can Enhance the Tolerance of Apple Rootstock M9-T337 Seedlings to Saline Alkali Stress by Initiating a Variety of Physiological and Biochemical Pathways - Jietao Zhai; Xulin Xian; Zhongxing Zhang; Yanxiu Wang (Plants)
Soil salinization severely restricts the growth and development of crops globally, especially in the northwest Loess Plateau, where apples constitute a pillar industry. Nanomaterials, leveraging their unique properties, can facilitate the transport of nutrients to crops, thereby enhancing plant growth and development under stress conditions. To investigate the effects of nano zinc oxide (ZnO NP) on the growth and physiological characteristics of apple self-rooted rootstock M9-T337 seedlings under saline alkali stress, one-year-old M9-T337 seedlings were used as experimental materials and ZnO NPs were used as donors for pot experiment. Six treatments were set up: CK (normal growth), SA (saline alkali stress,100 mmol/L NaCl + NaHCO3), T1 (saline alkali stress + 50 mg/L ZnO NPs), T2 (saline alkali stress + 100 mg/L ZnO NPs), T3 (saline alkali stress + 150 mg/L ZnO NPs) and T4 (saline alkali stress + 200 mg/L ZnO NPs). The results were found to show that saline alkali stress could significantly inhibit the growth and development of M9-T337 seedlings, reduce photosynthetic characteristics, and cause ion accumulation to trigger osmotic regulation system, endogenous hormone and antioxidant system imbalances. However, the biomass, plant height, stem diameter, total leaf area and leaf perimeter of M9-T337 seedlings were significantly increased after ZnO NP treatment. Specifically speaking, ZnO NPs can improve the photosynthetic capacity of M9-T337 by increasing the content of photosynthetic pigment, regulating photosynthetic intensity and chlorophyll fluorescence parameters. ZnO NPs can balance the osmotic adjustment system by increasing the contents of soluble protein (SP), soluble sugar (SS), proline (Pro) and starch, and can also enhance the activities of enzymatic (SOD, POD, and CAT) and non-enzymatic antioxidant enzymes (APX, AAO, GR, and MDHAR) to enhance the scavenging ability of reactive oxygen species (H2O2, O2•−), ultimately reducing oxidative damage; ZnO NPs promoted the growth of M9-T337 seedlings under saline alkali stress by synergistically responding to auxin (IAA), gibberellin (GA3), zeatin (ZT) and abscisic acid (ABA). Additionally, the Na+/K+ ratio was reduced by upregulating the expression of Na+ transporter genes (MdCAX5, MdCHX15, MdSOS1, and MdALT1) and downregulating the expression of K+ transporter genes (MdSKOR and MdNHX4). After comprehensive analysis of principal components and correlation, T3 (150 mg/L ZnO NPs) treatment possessed the best mitigation effect. In summary, 150 mg/L ZnO NPs(T3) can effectively maintain the hormone balance, osmotic balance and ion balance of plant cells by promoting the photosynthetic capacity of M9-T337 seedlings, and enhance the antioxidant defense mechanism, thereby improving the saline alkaline tolerance of M9-T337 seedlings.